Health studies in Lithuania : health sector development and its impact on national economy : working paper - Buivydas, Romualdas; Černiauskas, Nerijus; Dobravolskas, Algis (Ciklonas, 2013)
This study focused on the health system in Lithuania, recommendations for its development and on its impact on national economy. Intended for the professional public.
Keywords: Quality of Health Care; ekonomika; History, 21st Century; řízení veřejného zdraví; poskytování zdravotní péče; Delivery of Health Care; veřejné zdravotnictví; Economics; Lithuania; ekonomie, ekonomika, ekonomika zdravotnictví; Litva; Demography; dějiny 21. století; kvalita zdravotní péče; Public Health Administration; demografie